KAPASITAS ANTIOKSIDAN SUPLEMEN PADA BERBAGAI BERAT EKSTRAK BUBUK POD HUSK KAKAO - Partayasa, I nyoman; Kadir, Syahraeni; Rahim, Abdul (AGROTEKBIS, 2017)
The purpose of this study was to determine the best ratio of powdered cocoa pod husk for bio-capsule production and to determine damage of polyphenol powder and antioxidant after encapsulation ofcocoa pod husk. In this study, absolute ethanol solvent as a polar solvent was used to extract polyphenol compounds.  A Completely Randommized design with treatments of four different wieghts of cacao pod husk were used i.e. 20g, 25g, 30g and 35 g.  The highest capacity of antioxidant and supplement was shown by the 20 g cocoa pod husk treatment containing 11803.56 mg ascorbat, 83.15 g total phenol ase gallat.  This results indicate that the total phenol of the cacao pod husk decrease by 77.40% along with lowering antioxidant capacity by 18.66%.  Decreased level of the total phenol and antioxidant capacity is due to damage occuring during concenrating and drying proceses of the supplement materials. Keywords: Cocoa pod husk, Exraction and Supplements.